2015
DOI: 10.1063/1.4918710
|View full text |Cite|
|
Sign up to set email alerts
|

Spin-unrestricted random-phase approximation with range separation: Benchmark on atomization energies and reaction barrier heights

Abstract: We consider several spin-unrestricted random-phase approximation (RPA) variants for calculating correlation energies, with and without range separation, and test them on datasets of atomization energies and reaction barrier heights. We show that range separation greatly improves the accuracy of all RPA variants for these properties. Moreover, we show that a RPA variant with exchange, hereafter referred to as RPAx-SO2, first proposed by Szabo and Ostlund [A. Szabo and N. S. Ostlund, J. Chem. Phys. 67, 4351 (197… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 63 publications
3
38
1
Order By: Relevance
“…Most of these approximations account for the exchange interaction in RPA correlation and go beyond the SOSEX approximation. One of them is the rPT2 described above, but other approaches like RPAX2 42,43 and the recently developed RPAx-SO2 44 deliver also improvement beyond RPA. The AXK (approximate exchange kernel) approach is based on renormalization of the many-body perturbation theory (in a similar manner as rPT2) and provides a leading correction to RPA.…”
Section: Methodsmentioning
confidence: 99%
“…Most of these approximations account for the exchange interaction in RPA correlation and go beyond the SOSEX approximation. One of them is the rPT2 described above, but other approaches like RPAX2 42,43 and the recently developed RPAx-SO2 44 deliver also improvement beyond RPA. The AXK (approximate exchange kernel) approach is based on renormalization of the many-body perturbation theory (in a similar manner as rPT2) and provides a leading correction to RPA.…”
Section: Methodsmentioning
confidence: 99%
“…With srLDA as the underlying functional and no additional scaling of long-range correlation, the method performed similar to dRPA-srLDA on the aforementioned test sets, and gave slightly better result compared to the latter for activation and reaction enthalpies of 1,3-dipolar cycloadditions. 97 A study of Mussard et al 98,99 compared the accuracy of MP2-srDFT and RPA-srDFT for atomization energies from the AE49 dataset 100 and forward/reverse reaction barrier heights from the DBH24/08 dataset. 101 The RPAx-SO2-srDFT method with exchange, based on the Szabo and Ostlund's formulation, 102 combined with srPBE 21 was identified as one of the best-performing RPA schemes (the RPA correlation was not scaled).…”
Section: Thermochemistry and Kineticsmentioning
confidence: 99%
“…It was found that srDFT-lrRPA methods are particularly suitable to describe intermolecular interaction energies with good accuracies at a moderate computational cost in comparison with corresponding (full-range) wave function methods [54,75,76]. Moreover, several lrRPA methods have been tested for describing atomisation energies as well as a range of other thermokinetic properties and it has been observed that on average the range-separated RPA methods perform better than their full-range RPA counterparts [79,80]. Paier et al [79] could demonstrate that range-separated RPA approaches are able to resolve the strong delocalisation errors of the full-range RPA methods that lead to qualitatively wrong dissociation curves of some charged diatomic molecules.…”
Section: Introductionmentioning
confidence: 99%